2016
DOI: 10.1111/ijcs.12322
|View full text |Cite
|
Sign up to set email alerts
|

Consumer education and empowerment in Europe: recent developments in policy and practice

Abstract: This article develops the findings of an evaluation of European Commission consumer education, information and capacity building actions conducted in 2011, with an examination of action taken by 2016 to address the recommendations. Based on empirical research of documents, in-depth interviews, focus groups and semi-structured surveys of Directorate General for Health and Consumers and Directorate General for Education and Culture policy networks, it discusses the journey taken to improve consumer education and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This result is line with the previous study which showed that, despite the increase in the use of technologies, the consumer awareness of some key consumer rights remains limited, for example, in the EU. In the EU, only 9% of consumers are able to answer correctly all three knowledge questions on various issues such as unsolicited products, faulty product guarantees and distance purchase cooling off periods, with young people having the lowest levels of knowledge regarding consumer legislations (Brennan et al, 2016; European Commission, 2015). The consumer sovereignty study model by Knott, Zwick, and Schroeder (2006) emphasizes that rational consumer actions must be based on the knowledge and awareness of laws to allow them to deal with any issues between consumers and marketers in the marketplace.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is line with the previous study which showed that, despite the increase in the use of technologies, the consumer awareness of some key consumer rights remains limited, for example, in the EU. In the EU, only 9% of consumers are able to answer correctly all three knowledge questions on various issues such as unsolicited products, faulty product guarantees and distance purchase cooling off periods, with young people having the lowest levels of knowledge regarding consumer legislations (Brennan et al, 2016; European Commission, 2015). The consumer sovereignty study model by Knott, Zwick, and Schroeder (2006) emphasizes that rational consumer actions must be based on the knowledge and awareness of laws to allow them to deal with any issues between consumers and marketers in the marketplace.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the markets with all the development technologies in IR 4.0 have triggered all parties especially governments and consumer associations into enhancing the well‐being of consumers by empowering them to become more resilient, literate and wiser so that they can protect themselves in today’s challenging market (Nam, 2019). Despite the development of communication technologies such as social media, consumer awareness of some key consumer rights remains limited (Brennan, Vlaev, Blakemore, & Smith, 2016). For instance, the level of consumer protection knowledge reported in Hungary was generally insufficient and the level of their consumer awareness was extremely low (Szucs, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers need to be equipped with the relevant competences because they play a central role in childrenís consumer education. However, there has been a significant change in emphasis from the more prescriptive approaches to supporting, informing and mobilising teachers (Brennan, Vlaev, Blakemore, & Smith, 2017). An entrepreneurial and innovative spirit is needed; thus, teachers do not provide students with the answers, rather, they help them research and identify the right questions and find the best answers (European Commission, 2013).…”
Section: Overview Of Consumer Educationmentioning
confidence: 99%
“…Consumers' abilities to make proper decisions about household provisioning have an impact on their health and wellbeing (Palumbo 2016). Both institutional reports and literature identify the inability to shop as a characteristic of functionally illiterate consumers (e.g., Brennan et al 2017). The European Union (EU), United Nations Educational, Scientific and Cultural Organization (UNESCO), Organisation for Economic Cooperation and Development (OECD), and UN Environment Programme (UNEP) have identified a set of core abilities as fundamental to navigating the market.…”
Section: Consumer Abilities and Vulnerabilitymentioning
confidence: 99%